Lesson Study: Upaya Meningkatkan Kompetensi Pedagogis Guru melalui Supervisi Klinis di MI Nurul Ummah - Ratini (Jurnal Pendidikan Madrasah, 2019)
This research aims to improve the competency of teachers through clinical supervision activities. This research uses action research methods with a lesson study approach, conducted at MI Nurul Ummah. The lesson study conducted through three stages: planning, open learning, and reflection. The results of the research are in good category by fulfilling several indicators, namely 1) Students' learning motivation is increasing and the atmosphere of the class is more conducive, 2) increase in absorption and activity of students in class during study, 3) teachers more open, 4) teachers More motivated to seek out and explore a variety of learning methods or strategies, 5) Teachers learn from each other and cooperate in improving the quality of the teaching process through increased understanding not only about the material, but also Methods, media and learning aids, but also the assessment techniques used in the learning process obtained through the implementation, observation and reflection, 6) The teacher got a lot of enlightenment, apart from the peers, also from the Facilitators are always present to provide support, both when doing plan, do and see (reflection). With the presence of the facilitators, teachers have been increasingly enlightened and motivated to innovate innovations in learning. Lesson study can effectively improve the teacher pedagogical competence. This can be understood because the lesson study approach allows teachers to discuss the problems faced and discuss with other teachers to find solutions to the resolution.